The Divided Information Superhighway - Kuttner, Robert (Maine Policy Review, 1995)
This issue marks the introduction of the Margaret Chase Smith Essay, which will be a feature in each issue honoring Sen. Smith by focusing on issues related to citizenship, ethics in government, and integrity as a virtue of public leadership. In this first essay, economist Robert Kuttner asks some important ethical questions about the new world of electronic communications. He suggests that who plays and who pays are very important issues that have not been adequately considered in the highly technical and competitive world that will mark the 21st century. [This essay originally appeared as a column in the Boston Globe and is reprinted with [permission of the author.].
Keywords: information infrastructure